Power distribution engineering fundamentals and applications - Burke, James J. (Electrical engineering and electronics, 1994)
"Covering virtually all areas of distribution engineering, this complete reference work examines the unique behavior of utilities and provides the practical knowledge necessary to solve real-world distribution problems. "